2022
DOI: 10.7554/elife.79037
|View full text |Cite
|
Sign up to set email alerts
|

Selective endocytosis controls slit diaphragm maintenance and dynamics in Drosophila nephrocytes

Abstract: The kidneys generate about 180 liters of primary urine per day by filtration of plasma. An essential part of the filtration barrier is the slit diaphragm, a multiprotein complex containing nephrin as major component. Filter dysfunction typically manifests with proteinuria and mutations in endocytosis regulating genes were discovered as causes of proteinuria. However, it is unclear how endocytosis regulates the slit diaphragm and how the filtration barrier is maintained without either protein leakage or filter … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 47 publications
2
30
0
Order By: Relevance
“…Conversely, overexpression of Flot2 in podocytes attenuated cytoskeleton disruption and counteracted the reduction of SD proteins in lipid rafts, suggesting a role for Flot2 in recruiting these SD proteins into lipid rafts and mediating podocyte injury. A recent study also found that Flot2-mediated turnover of nephrin within the slit diaphragm is needed to maintain filter permeability in Drosophila nephrocytes 47 . This will further support the role of Flot2 in recruiting these SD proteins into lipid rafts and maintainning filtration barrier permeability.…”
Section: Discussionmentioning
confidence: 91%
“…Conversely, overexpression of Flot2 in podocytes attenuated cytoskeleton disruption and counteracted the reduction of SD proteins in lipid rafts, suggesting a role for Flot2 in recruiting these SD proteins into lipid rafts and mediating podocyte injury. A recent study also found that Flot2-mediated turnover of nephrin within the slit diaphragm is needed to maintain filter permeability in Drosophila nephrocytes 47 . This will further support the role of Flot2 in recruiting these SD proteins into lipid rafts and maintainning filtration barrier permeability.…”
Section: Discussionmentioning
confidence: 91%
“…Thus, overall, decreased interactions between Myo1e and CCVs result in a decrease in both CCV assembly (reduced density) and internalization (extended lifetimes), whereas prolonged interactions lead to the increased density and intensity of the CCVs. In a model of Drosophila nephrocytes, dynamin-dependent CME was recently shown to internalize nephrin proteins that are not in the lipid raft 59 . Thus, the interaction of Myo1e and dynamin may assist in maintaining a functional slit diaphragm and prevent filter clogging by removing defective nephrin 17 , 18 , 59 .…”
Section: Discussionmentioning
confidence: 99%
“…In a model of Drosophila nephrocytes, dynamin-dependent CME was recently shown to internalize nephrin proteins that are not in the lipid raft 59 . Thus, the interaction of Myo1e and dynamin may assist in maintaining a functional slit diaphragm and prevent filter clogging by removing defective nephrin 17 , 18 , 59 . Additional insight into Myo1e functions in CME may be gained in the future by using specific endocytic cargos in podocytes 60 to develop new endocytosis assays.…”
Section: Discussionmentioning
confidence: 99%
“…Nephrocyte live antibody labeling was performed as described elsewhere. 20 Briefly, nephrocytes carrying a genomic tag within the extracellular domain of fly nephrin were dissected in PBS and immediately exposed to the primary antibody (mouse anti-Myc, 9E10; DSHB, or sc-40; Santa Cruz Biotechnology, Dallas, TX, both 1:100) for 25 minutes at 4 C. Several brief washing steps with cold PBS followed, to remove the unbound antibody. The living cells now labeled with antibody were incubated at 29 C for the indicated time.…”
Section: Live Antibody Labeling and Internalizationmentioning
confidence: 99%
“…20 To examine the effect of Tbc1d8b loss-of-function on nephrin turnover directly, we used a knock-in of Myc into the locus of fly nephrin and performed live antibody labeling as previously described. 20 In this assay, living nephrocytes are labeled with Mycantibody ex vivo followed by tracking of the labeled nephrin 20 (schematic Figure 2A). In CRISPR/Cas9-mediated loss of Tbc1d8b we observed retention of live labeled nephrin on the surface after 2 hours, compared with control conditions (Figure 2, B-D).…”
Section: Tbc1d8b Is Specifically Required For Endocytosis Of Drosophi...mentioning
confidence: 99%